Structural characterization and anti-aging activity of a novel extracellular polysaccharide from fungus Phellinus sp. in a mammalian system. Issue 8 (13th July 2016) - Ma, Xiao-kui; Guo, Dan dan; Peterson, Eric Charles; Dun, Ying; Li, Dan yang
Abstract : A structurally new extracellular polysaccharide from Phellinus sp. culture, SHP-1, can alleviate oxidative damage and counteract aging and have a significant protective effect against oxidative stress or hepatotoxicity in mammalian system. Abstract : Little is known about the chemical structure of purified extracellular polysaccharides from Phellinus sp., a fungal species with known medicinal properties. A combination of IR spectroscopy, methylation analysis and NMR were performed for the structural analysis of a purified extracellular polysaccharide derived from Phellinus sp. culture, denoted as SHP-1, along with an evaluation of the anti-aging effect in vivo of the polysaccharide supplementation. The structure of SHP-1 was established, with a backbone composed of →2, 4)-α-d -glucopyranose-(1→ and →2)-β-d -mannopyranose-(1→ and two terminal glucopyranose branches. Biochemical analysis from mammalian animal experiments demonstrated that SHP-1 possesses the ability to enhance antioxidant enzyme activities, such as catalase (CAT) and superoxide dismutase (SOD) activities, Trolox equivalent antioxidant capacity (TEAC) in serum ofd -galactose-aged mice, while reducing lipofuscin levels, another indicator of cell aging, indicating a potential association with anti-aging activities in a dose dependent manner. This compound had a favourable influence on immune organ indices, and a marked amelioration ability of histopathological hepatic lesions such as necrosis, karyolysis and reduced inflammation and apoptosis in mouse hepatocytes. These results suggest that SHP-1 has strong antioxidant activities and a significant protective effect against oxidative stress or hepatotoxicity induced byd -galactose in mice and it could be developed as a food ingredient or a pharmaceutical to prevent many age-associated diseases such as major depressive disorder and hepatotoxicity. To our knowledge, this is the first report on the antioxidant effects of a novel purified exopolysaccharide derived from Phellinus sp.